Teorizar e medir: a pesquisa na gestão da imagem e da reputação - Panella, Cristina (Organicom, 2007)
Corporate communication ? and the work of its professionals ? has suffered from the absence of tools that allow them to measure their goals, image and reputation. We postulate that work carried out by teams can only be evaluated by using a systemic conception that takes into account the perceptions of the different stakeholders. The development of approaches and measuring tools should be preceded by a reflection that builds a theoretical/methodological support to which the survey professional (orsurveyour) has much to contribute.